PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP DISIPLIN GURU SEKOLAH DASAR DI KECAMATAN SINABOI KABUPATEN ROKAN HILIR - Nuzulina Nuzulina; Azhar Azhar; Dudung Burhanuddin (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
This research is motivated by phenomena such as some teachers who enter class not on time, some teachers do not fulfill teaching hours, some teachers leave their assignments during working hours, some teachers are late in making the realization of the work program that has been implemented. set. This study aims to analyze the contribution of two independent variables, namely the principal's leadership and organizational culture, and the dependent variable is teacher discipline at SDN Sinaboi District, Rokan Hilir Regency. To obtain the data needed, the writer uses descriptive statistical analysis techniques and inferential analysis. Based on the results of this study, it can be seen that 1) There is a significant and positive influence between the principal's leadership on teacher discipline at SDN Sinaboi District, Rokan Hilir Regency. This means that the better the principal's leadership, the better the teacher's discipline in carrying out their duties. 2) There is a significant and positive influence between organizational culture on teacher discipline at SDN Sinaboi District, Rokan Hilir Regency. This means that teacher discipline can be improved through a conducive organizational culture. 3) There is a joint influence of the principal's leadership and organizational culture on teacher discipline at SDN Sinaboi District, Rokan Hilir Regency. Principal leadership and organizational culture significantly determine and contribute to teacher discipline.